PEMANFAATAN KALIGRAFI DALAM ART COUNSELING UNTUK MENGURANGI STRES AKADEMIK SISWA - Vivi Sutinalvi (Yayasan Haiah Nusratul Islam, Indonesia, 2025)
Art counseling is a counseling method that uses art as the main tool to help people express their feelings, understand themselves, and find solutions to their problems. This method overcomes various emotional problems, including learning stress, which students often experience. Various sources of learning stress include environmental demands, academic pressure, and social expectations. All of these factors negatively impact students' mental, cognitive, and physical health. Calligraphy art therapy is one intervention method that has been proven to be effective. Students can overcome academic pressure in a creative and constructive way through calligraphy drawing activities, which makes them feel more relaxed and focused. Art counseling, especially calligraphy, can help students reduce learning stress in this article. Previous studies have shown that art can help people meditate and express negative emotions.